Clinical outcomes in cirrhotics with variceal or nonvariceal gastrointestinal bleeding: A prospective, multicenter cohort study. Issue 11 (13th July 2021) - Zullo, Angelo; Soncini, Marco; Bucci, Cristina; Marmo, Riccardo; ,
Abstract: Background and Aim: Upper gastrointestinal bleeding (UGIB) is associated with a distinct mortality in cirrhotics. We evaluated whether the rate of mortality and other outcomes differs between variceal and nonvariceal UGIB. Methods: This was a prospective, multicenter, cohort study on UGIB cirrhotics observed in 50 hospitals. Variceal or nonvariceal UGIB were diagnosed at endoscopy. The 6‐week mortality rate, need of blood transfusion, intensive care unit (ICU) admission, radiologic or surgical intervention, rebleeding rate, and length of stay in hospital were the main clinical outcomes compared. Data were analyzed at univariate and multivariate analysis, and odds ratio (OR) with their 95% confidence interval (CI) was calculated. Results: The study enrolled 706 cirrhotics, including 516 (73%) variceal and 190 (27%) nonvariceal UGIB. There were 78 (11%; 95% CI = 8.7–13.4) deceases, without any difference between variceal (11.0%) and nonvariceal (11.0%) groups. Child–Pugh score C (OR: 6.99; 95% CI = 2.58–18.95), and development of either hepatorenal syndrome (OR: 16.5; 95% CI = 7.02–38.9) or hepatic encephalopathy (OR: 2.38; 95% CI = 1.25–4.5) were independent predictors of mortality. Transfusions and onset of hepatic encephalopathy were significantly more frequent in variceal, whereas ICU admission rate was higher in nonvariceal bleedings. Overall, antibiotic prophylaxis was eventually administered in only 392 (55.5%) patients. Conclusions: Data found that the overall mortality rate in cirrhotics with UGIB seems to be reducing and that the value did not differ between variceal and nonvariceal types. Prevention of both hepatorenal syndrome and hepatic encephalopathy and implementation of antibiotic prophylaxis could improve survival in these patients.